Anthobium tectum Shavrin 2022, comb. nov. - Shavrin, Alexey V. (Zenodo, 2022)
Anthobium tectum (Paykull, 1789) comb. nov. (Figs. 2, 46–64, 69–81) Staphylinus tectus Paykull, 1789: 68; Paykull 1800: 411, Olivier 1795: 36 Omalium tectum : Gravenhorst 1806: 213; Gyllenhal 1810: 202; Olivier 1811: 478; C. Sahlberg 1827: 278, 1830: 282; Zetterstedt 1828: 49, 1838: 50; Lacordaire 1835: 487, 1854: 142; Laporte 1840: 191 Anthobium tectum : Curtis 1829: 28; Stephens 1834: 340 Deliphrum tectum : C. Sahlberg 1830: 282; Erichson 1839: 627, 1840: 872; Heer 1839: 187; Stephens 1839: 426; Redtenbacher 1849: 750, 1857: 249, 1874: 270; Fairmaire & Laboulbène 1856: 638; Kraatz 1857: 952; Calwer 1858: 199; Thomson 1859: 50, 1861: 197; Bach 1860: 270; Fauvel 1871: 121 [= 1872: 95]; Seidlitz 1875: 236; Calwer & Jäger 1876: 172; Mulsant & Rey 1880: 117; Fowler 1888: 406; Fauconnet 1892: 121; Ganglbauer 1895: 723; Luze 1905: 245; Reitter 1909: 188; Kuhnt 1913: 189; Johansen 1914: 597; Porta 1926: 25; Portevin 1929: 442; Scheerpeltz & Höfler 1948: 153; Hansen 1952: 77; Palm 1948: 98; Lohse 1964: 51; Focarile 1978: 36; Tóth 1982: 76 Deliphrum tectum var. picipennis J. Sahlberg, 1876: 246 [unavailable name] Deliphrum ( Deliphrum ) tectum : Zanetti, 1987: 286, 2012: 65 Omalium laeve Gravenhorst, 1806: 211; Olivier 1811: 477; Stephens 1834: 352, 1839: 429 Material examined: UK: 1 ♀: ‘ Scotland D. Sharp’ (BMNH); 1 ♂: Angleterre (IRSN); NORWAY: FINNMARK: 1 ♂: Bossekop. 07.1898 (BMNH); 1 ♀: Süd-Varanger, Pasvik-Järvi. 04.1944. G. Nietsch leg (MHNG); 1♂: Vadsö. A. Strand leg. (ZMUC); 1 ♀: Lyngen. J. Sahlberg leg. (MZHF); NORDLAND: 1 ♂: Kjeldvandet, 6 km S Sulitjelma, 67º4’N 16º3’E. 510 m a.s.l. 13.viii.1961 (BMNH); 1 ♂: Tysfjord (BMNH); 1 ♀: Nordmo. 17.07.2002. Schneider leg. (MZHF); TRØNDELAG: 1 ♂, 1 ♀: Kongsvold (BMNH); TELEMARK: 1 ♀: 5 km E Kalhovd. 60º04’N 8º23’E. 900-1100 m a.s.l. 27.07.1987. Munk leg. (ZMUC); TROMS: 3 ♂♂: Tromsö (IRSN, MZHF); INNLANDET: 1 ♂, 1 ♀: Dovre, Fokstua. 07.07.1933. H. Lindberg leg. (MZHF); OSLO: 1 ♀: Christiania. M. Cameron leg. (BMNH); 1 ♂, 1 ♀: Lövstad. 15.09.1975. T.E. Leiler leg. (SMNH); REGION NOT LOCATED: 1 ♀: ‘ Norwegen Munster’ (NMPC); 2 exs.: 09.1986. H. Gräf leg. (ZFMK); SWEDEN: LAPPLAND: 2 ♀♀: Abisko. 24.08.1927. L. Brundin leg. (SMNH); 1 ♂, 1 ♀: same data, 22.08.1927 (SMNH); 1 ♀: same data, 18.08.1927 (SMNH); 1 ♂: ‘ Lp. in.’, ‘ Bhn. ’ (SMNH); 1 ♂: Staloluokta, 67º19`N 16º19`E. 28.08.1961 (BMNH); 1 ♀: same data, 16.08.1962. T.E. Leiler leg. (SMNH); 1 ♀: Laukuluspa. 29.7.1980. T.E. Leiler leg. (SMNH); 2 ♀♀: Vastenje. T.E. Leiler leg. (SMNH); VÄSTERBOTTEN: 1 ♀: Lägsjön. 06.08.1951. Matthiessen leg. (SMNH); JÄMTLAND: 2 ♂♂: Fors. 16.07.1945. O. Lundblad leg. (SMNH); 1 ♂, 1 ♀: same data, 26.07.1945 (SMNH); 2 ♂♂: Frostviken. T. Palm (ZMUC); ÅNGERMANLAND: 2 ♂♂, 3 ♀♀: Graninge, Långsjön, 29.07.1945. O. Lundblad leg. (BMNH, SMNH); DALARNA: 1 ♂, 3 ♀♀: Kopparb, Hälsingg. 06.09.1950. O. Lundblad leg. (SMNH); 1 ♂, 1 ♀: same data. 06.09.1950. O. Lundblad leg. (SMNH); 1 ♂, 1 ♀: Kopparberg (BMNH); 1 ♂: Sundborn, Logärden. 25.07.1944. O. Lundblad leg. (SMNH); 1 ♀: ‘ Dlr. By sn. Th. Palm’ (ZMUC); UPPLAND: 2 ♂♂: Knivsta Noor. 01.04.1945. O. Lundblad leg. (SMNH); 2 ♂♂, 1♀: Fiby ur skog Vänge. 21.06.1945. O. Lundblad leg. (SMNH); 1 ♀: same data, 15.10.1945 (SMNH); 1 ♂: same data, 16.10.1947 (SMNH); 2 ♂♂: same data, 06.10.1946 (SMNH); 3 ♂♂, 2 ♀♀: Harparbol, Almunge. 16.10.1950. O. Lundblad leg. (SMNH); 1 ♀: Färingsö. T.E. Leiler leg. (SMNH); 1 ♂: Vallentung T.E. Leiler leg. (SMNH); 1 ♂: Almunge. 22.06.1961. T.E. Leiler leg. (SMNH); 1 ♀: Fåringsö. T.E. Leiler leg. (SMNH); 1 ♂: Vallentuna. T.E. Leiler leg. (SMNH); 1 ♀: Båtfors Alvkarleby. 12.9.1982. T.E. Leiler leg. (SMNH); 1 ♂, 2 ♀♀: same data. 30.9.1947. T.E. Leiler leg. (SMNH); 1 ♀: Naturpark Vårdsätra, Bondkyrka. 27.09.1951. O. Lundblad leg. (SMNH); 1 ♂: Stockholm. 18.10.1959. T. Leiler leg. (SMNH); 1 ♀: Nacka. 12.11.1967. T.E. Leiler leg. (SMNH); 1 ♀: Vesteräs-trakten. Sellman leg. (MZHF); SÖDERMANLAND: 1 ♀: Tullinga. 18.06.1930. P.H. Lindberg leg. (MZHF); 1 ♂: Trosa skärg. 5.10.1947. Matthiessen leg. (SMNH); 1 ♀: same data. 06.06.1949 (SMNH); SMÅLAND: 1 ♂: Edsbruk. 07.05.1964. T.E. Leiler leg. (SMNH); 1 ♂: Tranås (NMPC); 1 ♂, 1 ♀: ‘ Sm. ’, ‘ Bhn. ’ (SMNH); ÖSTERGÖTTLAND: 1 ♂: Ekön. 29.10.1961. Enuström leg. (SMNH); HALLAND: 1 ♀: Dagsås-tr. Hall. 26.10.1953. J.Th. Skovgaard leg. (ZMUC); GOTLAND: 1 ♀: Dalhem, Gotland. 04.06.1949. J.Th. Skovgaard leg. (ZMUC); REGION NOT LOCATED: 1 ♀: ‘ Suecia mer.’ (BMNH); 1 ex.: ‘ Suecia’ (ZIN); FINLAND: LAPLAND: 1 ♂: Majjanen. 08.09.1995. S. Blake leg. (BMNH); 1 ♀: Kjelvik (IRSN); OULU: 1 ♂: Kuhmo. Pitfall trap. 03.09.1989. V.N. Kashevarov leg. (cSh, ZMM); 1 ♀: Merikylä. 02.08.2001. O. Trottestam leg. (SMNH); EASTERN FINLAND: 1 ♂, 1 ♀: Suomuss. O. Sorsakoski leg. (NMPC); WESTERN FINLAND: 2 ♀♀: Lempäälä. M. Pohjola leg. (MZHF); REGION NOT LOCATED: 2 ♂♂: ‘ Fennia Reitter’ (MHNG); FRANCE: 1 ♂: Savoie. 1900 m a.s.l. 03.09.1993. D.A. Lott leg. (BMNH); SWITZERLAND: 1 ♂: Montana (BMNH); 1 ♂: Valais, Arolla. 07.1907 (BMNH); 1 ♂: Mayeus (BMNH); 1 ♂: Pontresina Grisons (MHNG); 1 ♂: Davoser Tal. 1500-1800 m a.s.l. 09.1934. Wolf leg. (MHNG); ITALY: 2 ♀♀: Val D`Aosta (Arvier), Val Grisanche. A. Focarille leg. (ZFMK); 2 ♂♂, 1 ♀: Abbazia (NMPC); 1 ♂: [Trentino-Alto Adige] Mendel Pass. 4400 ft. (BMNH); AUSTRIA: SALZBURG: 1 ♀: Tauern. P.E. Klimsch (MZHF); 1 ♂, 2 ♀♀: Hohe Tauern, Gasteiner Tal, Stockmann leg. (MZHF); 2 ♂♂, 2 ♀♀: Bad Gastein, Grüner Baum, 16- 30.09.1952. G. Benick leg. (MHNG); 1 ♂: Salzburg J. Handerek (MHNG); 1 ♀: Obersulzbachtal. 1700 m a.s.l. 10.09.1980. D. Erber leg. (MHNG); 1 ♂: Obersutzbach Tal. 08.08.1965 D. Erber leg. (MHNG); TYROL: 2 ♂♂: Mayrhofen, Zillert. 02- 15.09.1941. G. Benick leg. (BMNH); 1 ♂: Brasstein. 07.1913. A. Jedlička leg. (NMPC); 1 ♀: ‘ Tyrol’ (IRSN); 1 ♂: ‘ Tyrol Süd’ (MHNG); GERMANY: 1 ♀: Gotzenalm. 16.08.1936 (NMPC); REGION NOT LOCATED: 1 ex.: ‘ Germ. ’ (ZIN); 1 ♀: ‘ Saxonia’ (BMNH); CZECH REPUBLIC: KARLOVY VARY: 2 ♂♂: Sooş. L. Heyrovský leg. (NMPC); HRADEC KRÁLOVÉ: 1 ♂: Johannisbad. Rodt leg. (NMPC); CENTRAL BOHEMIA: 1 ♂, 1 ♀: Stromovka (NMPC); 1 ♂: Prague (MZHF); 1 ♀: ‘ Umgebung Prag Dr. Rodt’ (NMPC); 1 ♂: Pečky (NMPC); 1 ♂: Vrané. 16.05.1916. F. Rambousek leg. (MZHF); 2 ♂♂: Dobřickowitz. Rodt leg. (NMPC); SOUTH BOHEMIA: 1 ♀: Hartošice (NMPC); SOUTH MORAVIA: 1 ♀: Bruna. Fleischer leg. (NMPC); MORAVIA- SILESIA: 1 ♀: Lysa Hora. Klička leg. (NMPC); REGION NOT LOCATED: 2 exs.: ‘ Bohem. ’ (ZIN); 1 ♀: ‘ Bohemia’ (ZMUC); 1 ♀: ‘ Moravia Dr. Fleischer’ (NMPC); 1 ♀: ‘ Moravia Musc. ’ (NMPC); 1 ♀: ‘ Moravie’ (IRSN); SLOVAKIA: 1 ♂: Košice. 1919. Machulka leg. (NMPC); 1 ♂: Trenčin. J. Clermont leg. (MHNG); POLAND: 1 ♂: Tatra Mts., Koscieliska Valley. 330 ft. 24.06.1932 (BMNH); LITHUANIA: 1 ♂, 1 ♀: ‘ Zapole Dr. Kliška’, ‘ Pos. Válka Zirin Litva 1917’ (NMPC); LATVIA: DAUGAVPILS: 1 ♂: Ilgas. 12.10.2012. M. Janovska leg. (DUBC); REGION NOT LOCATED: 1 ♂: ‘ Bezkydy Dr. Jureček’ (NMPC); 1 ex: ‘ Livonia’ (ZIN); 1 ex.: ‘ Silesia’ (ZIN); RUSSIA: MURMANSK AREA: 1 ex.: Porchnikha, Rezvoy St. stream. 19.08.1928 (ZIN); 4 exs.: Kola Bay, Srednyaya guba. 28.08.1923. V.Yu. Fridolin leg. (ZIN); 1 ex.: same Bay, Yekaternininskiy Island. 18- 31.07.1900. Iljin leg. (ZIN); 24 exs: Alexandrovsk and Yekaterininskiy Island. 07.09.1925. V.Yu. Fridolin leg. (ZIN); 1 ♂: Kharlov Island, south shore. Under stones. 18.06.1985 (CS); 1 ex.: Lapland Biosphere Reserve. 10.08.1975. Sachevskaya leg. (ZIN); 3 exs.: same data. 21.08.1976 (ZIN); 1 ex.: Imandra. 10.0.1928. Stepanov leg. (ZIN); 1 ex.: Khibiny. 09.09.1928. Cheburova leg. (ZIN); 1 ♀: Khibiny, Kirovsk, botanical garden. 13- 23.09.1986. T.E. Rossolimo leg. (ZMM); 1 ex.: Kandalaksha Nature Reserve. In rotten Leccinum . 17.08.1963 (ZIN); KARELIA: 1 ♀: ‘ Sonostroff’, ‘ J. Sahlb. ’ (MZHF); LENINGRAD AREA: 3 exs.: Saint Petersburg, Olgino. 13.09.2008. V.N. Prasolov leg. (ZIN); 4 exs.: same data, Romanovka. 19.09.2008. (ZIN); 2 exs.: ‘ Petrop [olis].’ (ZIN); 1 ex.: Ligovo. 30.08.2003. G. Jakobson leg. (ZIN); 1 ex.: Taytsy. 05.06.1909. Shtakelberg leg. (ZIN); ARKHANGELSK AREA: 1 ♀: Severnaya. Betula forest. 25.07.1983 (cSh); 7 ♂♂, 13 ♀♀: ‘Fl. Mesen’, ‘B. Poppius’ (MZHF); 2 ♂♂: ‘Solovetsk’, ‘Levander’ (MZHF); TVER AREA: 1 ex.: Bologoye. 10.09.1904 (ZIN); MOSCOW AREA: 1 ex.: Boblovo. 06.05.1906. D. Smirnov leg. (ZIN); YAROSLAVL AREA: 32 exs.: ‘Яросл. У. [Yaroslavskiy uezd]’ (ZIN); KOMI: 2 exs.: Ukhta. Betula forest. 06.09.1975. V. Shilov leg. (ZIN); 1 ♀: ‘Petschora inf.’, ‘O. Kihlman’ (MZHF); NENETS AUTONOMOUS REGION: 2 ♂♂, 1 ♀: Maliy Gusinets. 05.08.2010. D. Pilate leg. (DUBC); KHANTY- MANSY AUTONOMOUS REGION: 3 ♂♂, 4 ♀♀: Sovetskiy District, Malaya Sosva Nature Reserve, right side of Malaya Sosva River near cordon Khangokurt, 61.95660°N 64.24860°E. 93 m a.s.l., in rotten fungi ( Boletus edulis , Russula spp., etc.) near forest road. 07.08.2018. A.B. Ryvkin leg. (cR, cSh, ZMM); 1 ♂, 2 ♀♀: Beryozovskiy District, Malaya Sosva Nature Reserve, left side of Malaya Sosva River, near cordon Shukhtungort, 62°39437’N 64°05248’E–62°37498’N 64°09415’E. 32–44 m a.s.l., in gill and pore geophilous fungi along forest road. 16.08.2018. A.B. Ryvkin leg. (ZMM); 2 ♂♂: same District and Nature Reserve, forest road NW cordon Shukhtungort, 62°38493’N 64°08145’E. 37 m a.s.l., in Boletus edulis and geophilous gill fungi. 26.08.2018. A.B. Ryvkin leg. (ZMM); 1 ♂: same District and Nature Reserve, Malaya Sosva River basin, forest road from cordon Shukhtungort to Svyatoy Sor Lake, 62°37498’N 64°09415’E–62°36748’N 64°05990’E. 32 m a.s.l., in geophilous gill fungi ( Amanita spp. etc.). 23.08.2018. A.B.Ryvkin leg. (ZMM); 2 ♂♂, 1 ♀: Surgutskiy District, Yuganskiy Nature Reserve, Bolshoy Yugan River, near cordon Kamenniy. In geophilous and epigenous fungi and mosses under those. 24.08.1999. A.B. Ryvkin leg. (cSh); 1 ♀: same data, 6-7 km downstream mouth of Sugmutenyakh River. In geophilous gill fungi. 21.08.2001 (ZMM); 1 ♀: same data, basin of Ay-Magromsy River, cordon Medvezhiy Ugol. Mosses and litter at the rill bank and at flood-plain with Calamagrostis sp., Ribes spp., Rosa sp., Filipendula ulmaria , Matteuccia struthiopteris , Equisetum sylvaticum , Sphagnum squarrosum , Sph . girgensohnii , Sph . spp., Plagiomnium sp. etc. (+15 C). 20.09.2002 (cR); 1 ♂, 1 ♀: same data, near cordon Medvezhiy Ugol. In geophilous and epigenous gill fungi (+12°C). 16.09.2002 (ZMM); 1 ♂: same data. In rotten Kuehneromyces mutabilis on trunks at flood-plain of stream (+15С). 20.09.2002 (ZMM); 1 ♂: same District and Nature Reserve, Vachempeu River (right confluent of Bolshoy Yugan River), 3 km SW of Kamenniy codon. In geophilous fungi ( Russula spp. etc.). 21.08.1999. A.B. Ryvkin leg. (ZMM); 1 ♂, 1 ♀: same data, Nyogus`yakh River near Kogonchina-2 field research station. River bank: Carex sp. and grasses. 30.08.2000 (ZMM); 2 ♀♀: same data, Nyogus`yakh River, Bisarkina field research station. Mosses and litter at slope swamp among flood-plain forest: Menyanthes trifoliate , Equisetum spp., Sphagnum squarrosum , S .? centrale , S . spp., Nardosmia frigida , Carex spp., Gramineae, Salix sp., Comarum palustre , Filipendula ulmaria ,? Tomenthypnum , Plagiomnium sp., etc. 27.07.1998 (ZMM); 1 ♂: same data, near S border of buffer zone of Yuganskiy Nature Reserve, Kolynlor Lake. Flotation of bait of rotten brown cap Boletus . 05.09.2001 (ZMM); 1 ♂: same District, environs of Ugut, basin of Ugutka River. In geophilous fungi. 20.08.1998. A.B. Ryvkin leg. (ZMM); SVERDLOVSK AREA: 1 ♀: Burmantovo. Pinus forest, in mushrooms. 23.07.1958. A. Rasnitsyn leg. (ZMM); CHELYABINSK AREA: 1 ♂: ‘Zlatoust Taganai’ (NMPC) 3 ♂♂: ‘Taganai: Ural 28.IX.1916 Dr. Jureček’ (NMPC); 1 ex.: Katav-Ivanovsk. 07.1926. Vakulenko leg. (ZIN); TYUMEN AREA: 1 ♂: Uvatskiy District., 8 km S Gornoslinkino, near Tobolsk Field Research Station of Severtsov Institute station. Mosses and litter in Betula forest at high flood-plain of left bank of Irtysh River: Carex globularis , grasses, Equisetum sylvaticum , etc. 30.09.2003. A.B. Ryvkin leg. (ZMM); 2 ♀♀: same data, 10 km S Gornoslinkino. In rotten Russula spp. 02.10.2003 (ZMM); 1 ♂, 1 ♀: same data. In geophilous gill and pore fungi. 10.09.2003 (ZMM); 1 ♂, 2 ♀♀: Kuznetsk Alatau Nature Reserve, delta of Malaya Bezymennaya Stream, ca. 15 air-km SSW of Belogorsk. 500 m a.s.l., Abies + Pinus taiga. 27- 31.08.1993. S. Golovatch & V. Gratchev leg. (cSh, ZMM); YAMALO- NENETS AUTONOMOUS REGION: 1 ex.: Yamburg. 06.06.2005. V.V. Barovskiy leg. (ZIN); NOVOSIBIRSK AREA: 1 ♀: Novosibirsk, Akademgorodok-Klyuchi. “Genetic” gardening. Forest, carrion traps. 21- 24.07.2008. V.K. & A.V. Zinchenko leg. (cSh); 2 ♂♂, 1 ♀: same data. Populus tremula forest, carrion, traps. 27- 31.08.2008. V.K. Zinchenko leg. (cSh); 1 ♂, 1 ♀: same data, 12- 14.09.2008. (cSh); 3 ♂♂, 4 ♀♀: same data, 03- 05.10.2008. (cSh); ALTAI: 1 ♂: Uymen River. 28.06.1960. A. Rasnitsyn leg. (ZMM); TOMSK AREA: 2 ♀♀: Tomsk, Kislovka. In mushrooms. 09.1972. A. Babenko leg. (ZMM); 1 ex.: Bolshoy Klyuch. A. Jakovlev leg. (ZIN); KRASNOYARSK TERRITORY: 2 ♂♂: Turukhanskiy District, 1-2 km E Mirnoye field research station, “Traktornaya” path. 40 m a.s.l., in rotten cep in forest. 28.08.1984. A.B. Ryvkin leg. (CR); 2 ♂♂, 2 ♀♀: Yeloguy Refuge, Yeloguy River 6 km below Tyna River mouth. In gill fungi ( Russula sp., etc.) in pine forest. 19- 22.08.1992. V.B. Semenov leg. (cSh, ZMM); 1 ♂, 1 ♀: same data. 15.08.1992 (ZMM); 1 ♀: same data, Yeloguy River, 30 km below Kellog, Kushnya River mouth. Forest with Pinus sylvestris , P . sibirica , Larix , Betula , Pleurozium , Hylocomium , in mushrooms and litter under those. 08.09.1993 (cSh); 1 ♂: same District, Kamennyi Dubches River, 30 km below Teulches River mouth. Pinus sibirica , Larix , Abies , Betula , Vaccinium vitis-idaea , V . myrtillus , Hylocomium , Pleurozium , Cladonia spp., in mosses. 20.09.1992. V.B. Semenov leg. (ZMM); 1 ♂: same data. Slope forest, in mosses (cR); 13 ♂♂, 11 ♀♀: same data, 3 km below Teulches River. Larix , Abies , Betula , Hylocomium , Pleurozium , Cladonia spp., Vaccinium vitis-idaea , V . myrtillus , in mosses. 17- 18.09.1992. V.B. Semenov leg. (cR, cSh, ZMM); 2 ♂♂: same data, 60 km below Teulches River, near hut. 150 m a.s.l., Pinus sibirica and Picea abies forest, with Betula , Polytrichum commune , Pleurozium and Hylocomium . 22.09.1992 (cSh); 4 ♂♂, 2 ♀♀: same data. Picea abies , with Pinus sibirica , Betula sp.: Polytrichum commune , Pleurozium schreberi , Hylocomium . 24.09.1992. V.B. Semenov leg. (cSh, ZMM); 25 ♂♂, 15 ♀♀: same District, basin of Podkamennaya Tunguska River, Rybnaya River (I), near seismological profile (about 40 km up-stream of river mouth). 175 m a.s.l., in gill fungi. 13.09.1990. A.B. Ryvkin leg. (cSh, ZMM); 1 ♀: same District, Goroshikha. 30.08.1994. L.B. Rybalov leg. (ZMM); 3 ♂♂: same District, Central Siberian Biosphere Reserve, Bolhaya Varlamovka River (VI), mouth of Malenkaya River. Litter and mosses in Betula , Picea and Larix forest with Equisetum sylvaticum , Polytrichum commune , Pleurozium , Hylocomium etc. 24.08.1988. A.B. Ryvkin leg. (ZMM); 1 ♂: Manskiy District, Stolby Nature Reserve, Bazaiskoye forestry, Bolshoy Synzhul Stream, 2 km up-stream of mouth. Mosses and litter in flood-plain and bank of stream. 15.08.1994. A.B. Ryvkin leg. (cR); EVENKIA: 1 ♀: Baykitskiy District, Central Siberian State Reserve, Stolbovaya River (I), 3 km below mouth of Dulkuma River. 85 m a.s.l., riverside drift near stream, flowing from swamp. 08.07.1990. A.B. Ryvkin leg. (ZMM); 1 ♂, 3 ♀♀: same District, basin of Podkamennaya Tunguska River, environs of Kuz`movka, near Kuz`movskiy Stream. 60 m a.s.l.. In rotten gill fungi and litter under those. 12.08.1989. A.B. Ryvkin leg. (ZMM); 1 ♀: same data, 110 m a.s.l., litter and mosses on slope near small streams with Alnus sp., Salix sp., Betula sp. etc. 04.10.1989 (ZMM); TUVA: 5 ♂♂, 4 ♀♀: Todzhenskiy District, Azas Nature Reserve, near cordon at Azas Lake. 940 m a.s.l., left bank of channel: silt and peat among sparse semiaquatic vegetation. 15.06.1991. A.B. Ryvkin leg. (cSh, ZMM); IRKUTSK AREA: 6 ♂♂, 6 ♀♀: Katangskiy District, left side of Chona River near mouth of Miringda River. 18- 25.08.2008. A.V. Shavrin & I. : Published as part of Shavrin, Alexey V., 2022, A revision of Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae Omaliinae: Anthophagini). V. Algidum, morosum and tectum groups, a new species of the fusculum group, and faunistic records, pp. 301-346 in Zootaxa 5104 (3) on pages 315-326, DOI: 10.11646/zootaxa.5104.3.1, http://zenodo.org/record/6332042 : {"references": ["Paykull, G. de. (1789) Monographia Staphylinorum Sueciae. J. Edman, Upsaliae, 8 + 81 pp. https: // doi. org / 10.5962 / bhl. title. 146996", "Paykull, G. de (1800) Fauna Suecica. Insecta. Tomus III. J. F. Edman, Upsaliae, 459 pp.", "Olivier, A. G. (1795) Entomologie, ou histoire naturelle des insectes, avec leur caracteres generiques et specifiques, leur description, leur synonymie, et leur figure illuminee. Coleopteres. Tome troisieme. Lanneau, Paris, 557 pp.", "Gravenhorst, J. L. C. (1806) Monographia Coleopterorum Micropterorum. Gottingae: Henricus Dieterich, 236 + [12] pp. https: // doi. org / 10.5962 / bhl. title. 67769", "Gyllenhal, L. (1810) Insecta Suecica descripta. Classis I. Coleoptera sive Eleuterata. Tomi I. Pars II. L. J. Leverentz, Scaris, xix + [1] + 660 pp.", "Olivier, A. G. (1811) Encyclopedie methodique, ou par ordre de matieres; par une societe de gens de lettres, de savans et d'artistes; precedee d'un vocabulaire universel, servant de table pour tout l'ouvrage, ornee des portraits de MM. Diderot & d'Alembert, premiers editeurs de l'encyclopedie. Histoire naturelle. Insectes. Tome huitieme. H. Agasse, Paris, 722 pp.", "Sahlberg, C. R. (1827) Pars 13. In: Insecta Fennica enumerans, dissertationibus academicis, A. 1817 - 1834 editis. Tomus I. Helsingforsiae, Frenckelliana, pp. 185 - 280.", "Sahlberg, C. R. (1830) Pars 19. In: Insecta Fennica enumerans, dissertationibus academicis, A. 1817 - 1834 editis. Tomus I. Helsingforsiae, Frenckelliana, pp. 281 - 360.", "Zetterstedt, J. W. (1828) Fauna insectorum Lapponica. Libraria Schulziana, Hammone, XX + 563 pp.", "Zetterstedt, J. W. (1838) Insecta lapponica descripta, Coleoptera. Leopoldi Voss, Lipsiae, 234 pp. [pp. 7 - 240]", "Lacordaire, J. T. (1835) Boisduval, J. & Lacordaire, J. T., Faune entomologique des environs de Paris; ou species general des insectes qui se trouvent dans un rayon de quinze a vingt lieues aux alentours de Paris. Tome Premier. Mequignon-Marvis, Paris, 696 pp.", "Lacordaire, J. T. (1854) Histoire naturelle des insectes. Genera des coleopteres ou expose methodique et critique de tous les genres proposes jusqu'ici dans cet ordre d'insectes. Tome deuxieme. Librairie Encyclopedique de Roret, Paris, 548 pp. https: // doi. org / 10.5962 / bhl. title. 8864", "Laporte [= Castelnau], F. L. N. C. de (1840) Histoire naturelle des insectes coleopteres. Tome premier. In: Histoire naturelle des animaux articules, annelides, crustaces, arachnides, myriapodes et insectes. Tome troisieme. P. Dumenil, Paris, cxxv + 324 pp.", "Curtis, J. (1829) A guide to an arrangement of British insects; being a catalogue of all the named species hitherto discovered in Great Britain and Ireland. J. Curtis, London, 256 columns.", "Stephens, J. F. (1834) Mandibulata. In: Illustrations of British entomology; or, a synopsis of indigenous insects: containing their generic and specific distinctions; with an account of their metamorphoses, times of appearance, localities, food, and economy, as far as practicable. Vol. V. Baldwin & Cradock, London, pp. 305 - 368.", "Erichson, W. F. (1839) Die Kafer der Mark Brandenburg. Erster Band. Zweite Abtheilung. Morin, Berlin, pp. 385 - 740.", "Erichson, W. F. (1840) Genera et species Staphylinorum insectorum coleopterorum familiae. (1). F. H. Morin, Berlin, pp. 401 - 954. https: // doi. org / 10.5962 / bhl. title. 59644", "Heer, O. (1839) Fauna Coleopterorum Helvetica. 1 (2). Orelii, Fuesslini et Sociorum, Turici, 216 pp. [pp. 145 - 360]", "Stephens, J. F. (1839) A manual of British Coleoptera, or beetles; containing a brief description of all the species of beetles hitherto ascertained to inhabit Great Britain and Ireland; together with a notice of their chief localities, times and places of appearances, etc. Longman, Orme, Brown, Green, and Longmans, London, xii + 443 pp. https: // doi. org / 10.5962 / bhl. title. 59227", "Redtenbacher, L. (1849) Bogen. In: Fauna Austriaca. Die Kafer. Nach der analytischen Methode bearbeitet. C. Gerold, Wien, pp. 41 - 58. https: // doi. org / 10.5962 / bhl. title. 37851", "Redtenbacher, L. (1857) Fauna Austriaca. Die Kafer. Nach der analytischen Methode bearbeitet. Zweite, ganzlich umgearbeitete, mit mehreren Hunderten von Arten und mit der Charakteristik sammtlicher europaischen Kafergattungen vermehrte Auflage. C. Gerold's Sohn, Wien, pp. 129 - 976. [1856 - 1858] https: // doi. org / 10.5962 / bhl. title. 9570", "Redtenbacher, L. (1874) Fauna Austriaca. Die Kafer, nach der analytischen Methode bearbeitet. Dritte, ganzlich umgearbeitete und beteutend vermehrte Auflage. C. Gerolds Sohn, Wien, 564 + 571 + viii + cliii pp., 2 pls.", "Fairmaire, L. & Laboulbene, A. (1856) Faune entomologique francaise ou description des insectes qui se trouvent en France. Coleopteres. Vol. 1. Liv. 3. Deyrolle, Paris, pp. 371 - 665.", "Kraatz, G. (1857) Naturgeschichte der Insecten Deutschlands. Erste Abtheilung Coleoptera. Zweiter Band. Lieferung 3 - 6. Nicolai, Berlin, 704 pp. [pp. 377 - 1080]", "Calwer, C. G. (1858) Kaferbuch. Allgemeine und specielle Naturgeschichte der Kafer Europa's nebst der Anweisung sie zu sammeln und aufbewahren. Krais & Hoffmann, Stuttgart, xxviii + 788 pp.", "Thomson, C. G. (1859) Skandinaviens Coleoptera, synoptiskt bearbetade. Vol 1. Berlingska Boktryckeriet, Lund, 290 pp. https: // doi. org / 10.5962 / bhl. title. 138677", "Thomson, C. G. (1861) Skandinaviens Coleoptera, synoptiskt bearbetade. Vol. 3. Berlingska Boktryckeriet, Lund, 278 pp.", "Bach, M. (1860) Kaferfauna fur Nord- und Mitteldeutschland mit besonderer Rucksicht auf die preussischen Rheinlande. IV. Band. J. Holscher, Coblenz, 4 nlb., 292 str.", "Fauvel, A. (1871) Faune Gallo-Rhenane ou descriptions des insectes qui habitent la France, la Belgique, la Hollande, le Luxembourg, les provinces Rhenanes et la Valais avec tableaux synoptiques et planches gravees. Bulletin de la Societe Linneenne de Normandie, Series 2, 5 (1869 - 1870), 27 - 192.", "Fauvel, A. (1872) Faune Gallo-Rhenane ou species des insectes qui habitent la France, la Belgique, la Hollande, le Luxembourg, la prusse Rhenane, la Nassau et la Valais avec tableaux synoptiques et planches gravees. Vol. 3. Liv. 3. Le Branc- Hardel, Caen, 214 pp.", "Seidlitz, G. (1875) Fauna Baltica. Die Kafer (Coleoptera) der Ostseeprovinzen Russlands. Dorpater Naturforscher-Gesellschaft Verlag, Dorpat, xlii + 560 pp.", "Calwer, C. G. & Jager, G. (1876) Calwers Kaferbuch. Naturgeschichte der Kafer Europas. Zum Handgebrauche fur Sammler. 4. Auflage. J. Hoffman, Stuttgart, 835 pp.", "Mulsant, E. & Rey, C. (1880) Histoire naturelle des Coleopteres de France. Tribu des brevipennes. Onzieme famille: Omaliens. Douxieme famille: Pholidiens. Annales de la Societe Linneenne de Lyon, Series 2, 27, 1 - 430. https: // doi. org / 10.3406 / linly. 1880.3986", "Fowler, W. W. (1888) The Coleoptera of the British Islands. A descriptive account of the families genera, and species indigenous to Great Britain and Ireland, with notes as to localities, habitat, etc. Vol. 2. Staphylinidae. L. Reeve & co., London, 444 pp. https: // doi. org / 10.5962 / bhl. title. 29517", "Fauconnet, L. (1892) Faune analytique des Coleopteres de France. Bligny-Cottot, Autun, 528 pp.", "Ganglbauer, L. (1895) Die Kafer von Mitteleuropa. 2. Familienreihe Staphylinoidea. Theil I. Staphylinidae, Pselaphidae. Carl Gerold's Sohn, Wien, 881 pp.", "Luze, G. (1905) Revision der palaarktischen Arten der Staphyliniden-Gattung Lathrimaeum Er. Verhandlungen der Kaiserlich- Koniglichen Zoologisch-Botanischen Gesellschaft in Wien, 55, 53 - 69.", "Reitter, E. (1909) Fauna Germanica. Die Kafer des Deutschen Reiche. Nach der analytischen Methode bearbeitet. II Band. Schriften des Deutschen Lehrervereins fur Naturkunde 24. K. G. Lutz, Stuttgart, 392 pp., pls. 41 - 80.", "Kuhnt, P. (1913) Illustrierte Bestimmungs-Tabellen der Kafer Deutschlands. Ein Handbuch zum genauen und leichten Bestimmen aller in Deutschland vorkommenden Kafer. E. Schweizterbart, Stuttgart, VTI + 1138.", "Johansen, J. P. (1914) Danmarks rovbiller eller Billefam. Staphylinidae's danske Slaegter og Arter. Bianco Lunos Bogtrykkeri, Kobenhavn, 660 pp.", "Porta, A. (1926) Fauna Coleopterorum Italica. Vol. II. Staphylinoidea. Stailimente Tipografico Piacentino, Piacenza, 405 pp.", "Portevin, G. (1929) Histoire naturelle des Coleopteres de France. I. Adephaga. Polyphaga: Staphylinoidea. In: Encyclopedie Entomologique. Vol. 12. P. Lechevalier, Paris, pp. i - xii + 1 - 649.", "Scheerpeltz, O. & Hofler, K. (1948) Kafer und Pilzer. Jugend und Volk, Wien, 351 pp.", "Hansen, V. (1952) Biller XV. Rovbiller, 1. In: Danmarks Fauna. Vol. 57. G. E. C. Gads Forlag, Kobenhavn, 274 pp.", "Palm, T. (1948) Svensk Insekfauna. 9. Skalbaggar. Coleoptera. Kortvingar: Fam. Staphylinidae. Unterfam. Micropeplinae, Phloeocharinae, Olisthaerinae, Proteininae, Omaliinae. Almquist and Wiksells, Uppsala, 133 pp.", "Lohse, G. A. (1964) Staphylinidae I. (Micropeplinae bis Tachyporinae). In: Freude, H., Harde, K. & Lohse, G. (Eds.), Die Kafer Mitteleuropas. Band 4. Goecke & Evers, Krefeld, 264 pp.", "Focarile, A. (1978) Interessanti coleotteri della Valle d'Aosta. Series 2. Revue Valdotaine d'Histoire Naturelle, 32, 27 - 76.", "Toth, L. (1982) Magyarorszag Allatvilaga - Fauna Hungariae, Holyvak II. - Staphylinidae II VII. Akademiai Kiado, Budapest, 110 pp.", "Sahlberg, J. (1876) Enumeratio coleopterorum brachypterorum Fenniae. Systematisk forteckning ofver de inom Finlands naturalhistoriska omrade hittils funna Coleoptera Brachelytra jemte uppgift om arternas utbredning och beskrifningar af nya och mindre kanda species. I. Staphylinidae. Acta Societatis pro Fauna Flora Fennica, 1, 1 - 248.", "Zanetti, A. (1987) Coleoptera. Staphylinidae. Omaliinae. In: Fauna d'Italia. Vol. 25. Calderini, Bologna, pp. i - xii + 1 - 472.", "Zanetti, A. (2012) Unterfamilie Omaliinae. In: Assing, V. & Schulke, M. (Eds.), Freude-Harde-Lohse-Klausnitzer - Die Kafer Mitteleuropas. Band 4. Staphylinidae I. Zweite neubearbeitete Auflage. Spektrum Akademischer Verlag, Heidelberg, pp. 49 - 117.", "Horion, A. (1963) Faunistik der mitteleuropaischen Kafer. Band IX: Staphylinidae. 1. Teil. Micropeplinae bis Euaesthetinae. Band 9. A. Feyel, Uberlingen-Bodensee, xii + 412 pp.", "Herman, L. H. (2001) Catalogue of the Staphylinidae (Insecta: Coleoptera). 1758 to the end of the second millenium. Bulletin of the American Museum of Natural History, 265 (1 - 7), i - vi + 1 - 4218. https: // doi. org / 10.1206 / 0003 - 0090.265.1.1", "Silfverberg, H. (1988) Lists of the insect types in the Zoological Museum, University of Helsinki. 8. Coleoptera: Staphylinidae. Acta Entomologica Fennica, 52, 15 - 40.", "Pearson, R. G. (1962) The Coleoptera from a Late Glacial deposit at St. Bees, West Cumberland. Journal of Animal Ecology, 31, 129 - 150. https: // doi. org / 10.2307 / 2335"]}